2022
DOI: 10.1080/17482631.2022.2066256
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant women’s experiences with Norwegian maternal health services: implications for policy and practice

Abstract: Purpose Navigating a health system which differs considerably from one’s own can be a challenging process. Navigating this in seeking maternal health care can be additionally daunting. This article explores how immigrant women from diverse countries and ethnic backgrounds experienced and navigated the Norwegian maternal health service during pregnancy and childbirth. Method Eleven semi-structured interviews collected between 2019 to 2020 and analysed thematically inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Women’s previous experiences from, and familiarity with, other health care system, socio-cultural values and practices, as well as health literacy more broadly influence the use of antenatal care [ 45 , 58 ]. However, structural vulnerabilities, such as restricted access, low or no income, degrees of dependency on others, and psychosocial hardship, might have a stronger influence on their ability to access adequate antenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Women’s previous experiences from, and familiarity with, other health care system, socio-cultural values and practices, as well as health literacy more broadly influence the use of antenatal care [ 45 , 58 ]. However, structural vulnerabilities, such as restricted access, low or no income, degrees of dependency on others, and psychosocial hardship, might have a stronger influence on their ability to access adequate antenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…As the findings above suggest, trust is not static. Migrant women's expectations and their unfulfilled expectations of the care system (in Norway) can lead to distrust at the meso-level, which means distrust in the care system (Mehrara et al, 2022). Distrust can be reversed by the gradual building of individual trust between a woman and a particular health professional.…”
Section: Importance Of Trust In Maternity Carementioning
confidence: 99%
“…Ng and Newbold (2011) found that 'often, differences in cultural expectations or knowledge of different cultural groups resulted in less than optimal consultations' (p. 566), one of the reasons being that immigrant women 'may feel that they are not receiving appropriate care when their cultural needs are not being met' (p. 566). Lastly, Mehrara et al (2022) presented that some immigrant women found Norway's approach to maternity care to be less medicalized in comparison to that of their home countries, which consequently hindered their trust in it. This speaks directly to the encountered differences between cultural health models that extend beyond a concern for immigrants' knowledge or language barriers.…”
Section: More Than Health Carementioning
confidence: 99%